O que é vida? de Erwin Schrödinger: caminhos nas ciências da vida, 1933-2013 - Silva, Alex Costa da (2016)
What Is Life?,a set of lectures delivered in 1943, consisted in speculations made by a physicist and Nobel Laureate, Erwin Schrödinger, on a subject apparently alien to his field of expertise, namely, the nature of life. Published as a small book with the same title, those lectures were widely read, called the attention of scholars from many fields of knowledge and found correspondence in a large part ofthe conceptual grounds of the molecular biology of the second half of the 20th century. Schrödinger s ideas did not lose interest, to the point they were celebrated 50 and 70 years later in scientific meetings also namedWhat Is Life? In the present study we first sought to elucidate the reasons for Schrödinger to have chosen the nature of life as the subject of his lectures. Then we investigated the contemporary reception to the ideas discussed in them. Third we analyzed several or the presentations made by reputed scientists in the 1993 meeting aiming to establish the relevance of Schrödinger s ideas for the development of the life sciences in the course of those 50 years. Finally we emphasize the interest such ideas still arose 20 years later, as reflected in the specialized media and more particularly by J.C.Venter, one of the first to sequence the human genome, in the last What Is Life?lecture, from 2013, this time focusing on the 21st century perspective